Reduced survival of Steller sea lions in the Gulf of Alaska following marine heatwave - Hastings, Kelly K.; Gelatt, Thomas S.; Maniscalco, John M.; Jemison, Lauri A.; Towell, Rod; Pendleton, Grey W.; Johnson, Devin S. (Frontiers in Marine Science, 2023)
The North Pacific marine heatwave of 2014–2016 (PMH), one of the most geographically-extensive and severe marine heatwaves on record, resulted in widespread and persistent perturbation of the Gulf of Alaska and California Current ecosystems. Negative effects of the PMH on marine mammals have been observed, but are not yet well understood. The endangered Steller sea lion Eumetopias jubatus is an important top predator in the Gulf of Alaska that is also particularly vulnerable to sudden or severe ecosystem shifts. We examined survival of 4,178 known-aged Steller sea lions marked from 2000 to 2016 from Kodiak Island through Southeast Alaska, using mark-recapture models and 12,811 resightings collected from 2001 to 2021. Survival of adult females aged 3–15 was reduced -0.05 to -0.23 during the PMH in the areas east, but not west, of Cook Inlet. Survival of Kodiak females was unaffected by the PMH, but survival of Sugarloaf females aged 5–8 was reduced -0.13 from summer 2015 to summer 2016. Lowest survival in Southeast Alaska occurred from summer 2016 to summer 2017, but was also reduced from summer 2014 to summer 2016. Reduced survival continued post-PMH in Kenai Peninsula/Prince William Sound, but not in Southeast Alaska. Survival of adult males was insensitive to the PMH, except in Southeast Alaska where male survival was reduced -0.25 from summer 2016 to summer 2017. Prolonged or intermittent high adult female mortality may reduce population growth and initiate regional declines. Survival response of Steller sea lions to the PMH varied regionally despite similar patterns of ocean warming throughout our study area, suggesting areas east versus west of Cook Inlet were affected differently by the PMH, perhaps due to habitat and oceanographic differences.